Misconceptions in radicals in high school mathematics - Ozkan, Erdogan Mehmet (ELSEVIER SCIENCE BV, 2011)
The aim of this study was to determine misconceptions of the radicals of the high school students that attend 9 class. The samples of study consists of the students of an Anatolian High School in Istanbul, Turkey. Some sample questions are asked to related students to understand the misconceptions. According to the result of the study, it is seen that the students have misconseptions about radicals. Some solutions are recommended to those students to overcome such difficulties. (C) 2011 Published by Elsevier Ltd. Open access under CC BY-NC-ND license.
Keywords: Mathematics Education; Root Numbers; Misconceptions; Education & Educational Research